1994
DOI: 10.1063/1.530441
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of the eigenfunctions for the Caudrey–Beals–Coifman system

Abstract: The direct and the inverse scattering problem for the first order linear systems of the type Lψ(x,λ)≡(i(d/dx)+q(x)−λJ)ψ(x,λ)=0, J∈𝔥, q(x)∈𝔤J , which generalizes the Zakharov–Shabat system and the systems studied by Caudrey, Beals, and Coifman (CBC) is analyzed herein. Here J is a regular complex constant element of the Cartan subalgebra 𝔥⊆𝔤 of the simple Lie algebra 𝔤 and the potential q(x) vanishes fast enough for ‖x‖ → ∞ taking values in the image 𝔤J of adJ. The CBC results are generalized and the fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
180
0
13

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(195 citation statements)
references
References 47 publications
2
180
0
13
Order By: Relevance
“…Beals and Coifman showed that any potential can be approximated to arbitrary accuracy with a potential on a finite support [65]. This result was later generalized to potential with coefficients from any finite-dimensional simple Lie algebra [11]. Reformulating the general results of [11,32], for the particular choice of the algebra D 4 ≃ so(8) we find that 1.…”
Section: Spectral Properties Of L and Fundamental Analytic Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beals and Coifman showed that any potential can be approximated to arbitrary accuracy with a potential on a finite support [65]. This result was later generalized to potential with coefficients from any finite-dimensional simple Lie algebra [11]. Reformulating the general results of [11,32], for the particular choice of the algebra D 4 ≃ so(8) we find that 1.…”
Section: Spectral Properties Of L and Fundamental Analytic Solutionsmentioning
confidence: 99%
“…This result was later generalized to potential with coefficients from any finite-dimensional simple Lie algebra [11]. Reformulating the general results of [11,32], for the particular choice of the algebra D 4 ≃ so(8) we find that 1. The continuous spectrum of L fills up the set of rays l ν , ν = 0, .…”
Section: Spectral Properties Of L and Fundamental Analytic Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining the ideas of [7] with the symmetries of the potential (1.6) we can construct a set of 2h fundamental analytic solutions (FAS) m ν (x, t, λ) of (2.1) and prove that:…”
Section: The Spectral Properties Of Lmentioning
confidence: 99%
“…Then the construction of the fundamental analytic solutions and the solution of the corresponding inverse scattering problem for (1.2) becomes more difficult [11,12].…”
Section: Introductionmentioning
confidence: 99%